Enrichment of functional CD8 memory T cells specific for MUC1 in bone marrow of patients with multiple myeloma - Choi, Carmen; Witzens-Harig, Mathias; Bucur, Marianna; Feuerer, Markus; Sommerfeldt, Nora; Trojan, Andreas; Ho, Anthony Dick; Schirrmacher, Volker; Goldschmidt, Hartmut; Beckhove, Philipp (Blood, 2005)
Multiple myeloma (MM) is one of the most common hematologic malignancies. Despite extensive therapeutical approaches, cures remain rare exceptions. An important issue for future immunologic treatments is the characterization of appropriate tumor-associated antigens. Recently, a highly glycosylated mucin MUC1 was detected on a majority of multiple myeloma cell lines. We analyzed bone marrow and peripheral blood of 68 patients with HLA-A2-positive myeloma for the presence and functional activity of CD8 T cells specific for the MUC1-derived peptide LLLLTVLTV. Forty-four percent of the patients with MM contained elevated frequencies of MUC1-specific CD8 T cells in freshly isolated samples from peripheral blood (PB) or bone marrow (BM) compared with corresponding samples from healthy donors. BM-residing T cells possessed a higher functional capacity upon specific reactivation than PB-derived T cells with regard to interferon γ (IFN-γ) secretion, perforin production, and cytotoxicity.
Prepublished online as Blood first edition paper, November 23, 2004
Gesehen am 25.02.2022